2011
DOI: 10.1016/j.jaad.2011.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in cutaneous melanoma incidence and death rates in the United States, 1992-2006

Abstract: The continued increases in melanoma death rates for older persons and for thin lesions suggest that the increases may partly reflect increased ultraviolet radiation exposure. The substantial contribution of thin lesions to melanoma mortality underscores the importance of standard wide excision techniques and the need for molecular characterization of the lesions for aggressive forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
249
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(267 citation statements)
references
References 31 publications
(33 reference statements)
9
249
1
8
Order By: Relevance
“…Of those, 126 were posts in the Facebook News Feed, 379 were Tweets in the Twitter Timeline, 106 were Twitter retweets, 27 were tanning club emails, and 24 were Yipit deals on indoor tanning services. We found no sidebar advertisements and no sponsored News Feed posts on Facebook from indoor The data collection period was 10 days for Facebook, 38 days for Tweets, 32 days for retweets, and 39 days for both Yipit deals and email clubs 2 We selected only four indoor tanning salons in Akron because we were unable to identify five that met our inclusion criteria. Other salon services-spa, teeth whitening, red light therapy, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, 126 were posts in the Facebook News Feed, 379 were Tweets in the Twitter Timeline, 106 were Twitter retweets, 27 were tanning club emails, and 24 were Yipit deals on indoor tanning services. We found no sidebar advertisements and no sponsored News Feed posts on Facebook from indoor The data collection period was 10 days for Facebook, 38 days for Tweets, 32 days for retweets, and 39 days for both Yipit deals and email clubs 2 We selected only four indoor tanning salons in Akron because we were unable to identify five that met our inclusion criteria. Other salon services-spa, teeth whitening, red light therapy, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Indoor tanning, Skin cancer, Social media, Advertising BACKGROUND Skin cancer incidence is rising and is increasingly affecting adolescents and young adults, creating a profound social and economic burden in the USA [1][2][3][4][5][6][7][8][9][10][11]. Ultraviolet (UV) exposure is the primary and preventable risk factor for skin cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Melanoma causes more deaths than any other skin cancer, and its incidence is increasing, particularly among non-Hispanic whites and women; increases have also been noted among all tumor thicknesses. 18 Additionally, melanoma is one of the most commonly diagnosed cancers among adolescents and young adults in the U.S. 19,20 Indoor tanning before age 35 years increases the risk of melanoma by 60%-80% or more, possibly because of longer duration of use. 3,13,16,21 In addition to the morbidity and mortality it causes, skin cancer poses a substantial economic burden in the U.S. 22,23 The treatment of melanoma and nonmelanoma skin cancer costs an estimated $1.7 billion each year.…”
Section: Indoor Tanning and Cancer Riskmentioning
confidence: 99%
“…24 Continued research into skin cancer is critical, as studies have shown an increase in the incidence of melanoma and nonmelanoma skin cancers. 25,26 We acknowledge limitations in our study. Access to journal articles was limited by our university's subscriptions.…”
Section: Discussionmentioning
confidence: 98%